Turning molehills into mountains: Sleepiness increases workplace interpretive bias - Barber, Larissa K.; Budnick, Christopher J. (Journal of Organizational Behavior, 2015)
Three studies draw from evolutionary theory to assess whether sleepiness increases interpretive biases in workplace social judgments. Study 1 established a relationship between sleepiness and interpretive bias using ambiguous interpersonal scenarios from a measure commonly used in personnel selection (N = 148). Study 2 explored the boundary conditions of the sleepiness–interpretive bias link via an experimental online field survey of U.S. adults (N = 433). Sleepiness increased interpretive bias when social threats were clearly present (unfair workplace) but did not affect bias in the absence of threat (fair workplace). Study 3 replicated and extended findings from the previous two studies using objective measures of sleep loss and a quasi-experimental manipulation of minor sleep loss (N = 175). Negative affect, ego depletion, or personality variables did not influence the observed relationships. Overall, results suggest that a self-protection/evolutionary perspective best explains the effects of sleepiness on workplace interpretive biases. These studies advance the current research on sleep in organizations by adding a cognitive “threat interpretation” bias approach to past work examining the emotional reaction/behavioral side of sleep disruption. Interpretive biases due to sleepiness may have significant implications for employee health and counterproductive behavior. Copyright © 2015 John Wiley & Sons, Ltd.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/job.1992
Keywords: Conditional Reasoning Test of Aggression; dept.psy; fairness; interpretive bias; sleep; work perceptions

Very-Brief, Web-Based Interventions for Reducing Alcohol Use and Related Problems among College Students: A Review. - Leeman, Robert F; Perez, Elliottnell; Nogueira, Christine; DeMartini, Kelly S (Frontiers in psychiatry, 2015)
Very-brief, web-based alcohol interventions have great potential due to their convenience, ease of dissemination, and college students' stated preference for this intervention modality. To address the efficacy of these interventions, we conducted a review of the literature to identify randomized controlled trials (RCTs). Fifteen published reports were included. All RCTs meeting criteria for inclusion tested an intervention that featured personalized feedback on students' patterns of alcohol consumption. This review found some evidence to support the efficacy of very-brief, web-based interventions among college students for alcohol use reduction. Several trials, however, reported no evidence of efficacy and the methods of multiple trials raised concerns about potential bias that may have influenced study results. By contrast, this review did not yield evidence to support the efficacy of very-brief, web-based interventions for reduction of alcohol–related problems among college students. We found evidence to support the efficacy of two main types of intervention content: (a) focused solely on personalized normative feedback designed to correct misconceptions about peer alcohol consumption and (b) multi-component interventions. Future research is needed to test enhancements to very-brief, web-based interventions that feature personalized feedback on patterns of alcohol use and to determine for which types of college drinkers (e.g., heavier or lighter drinkers) these interventions are most efficacious. In addition, future studies are needed to test novel, very-brief, web-based interventions featuring approaches other than personalized feedback. In summary, this review yielded some evidence supporting very-brief, web-based interventions in reducing alcohol use but not related problems in college students. Very-brief, web-based interventions are worth pursuing given their convenience, privacy, and potential public health benefit.
21 citations (Crossref) [2023-10-31] Place: Switzerland Leeman, Robert F. Department of Psychiatry, Yale School of Medicine, New Haven, CT, USA. Perez, Elliottnell. Department of Psychology, Southern Connecticut State University, New Haven, CT, USA. Nogueira, Christine. Department of Psychiatry, Yale School of Medicine, New Haven, CT, USA. DeMartini, Kelly S. Department of Psychiatry, Yale School of Medicine, New Haven, CT, USA.
Keywords: Computer; Effectiveness; Intervention; Motivational interviewing; Prevention; Review; Technology; Young adult; Youth; alcohol consumption; attitude to health; college student; dept.psy; evidence based practice; follow up; human; outcome assessment; peer group; peer-reviewed; personalized feedback; public health service; randomized controlled trial (topic); sample size; systematic error; very brief web based intervention

Should police use ACID? Training and credibility assessment using transcripts versus recordings - Colwell, Kevin; James-Kangal, Neslihan; Hiscock-Anisman, Cheryl; Phelan, Vivian (Journal of Forensic Psychology Practice, 2015)
There is a need for an applicable system of investigative interviewing and credibility assessment that extends science to practice. Experiment 1: Officers assessed the credibility of colleagues in a face-to-face interaction. Fourteen of sixteen officers were wrong in determining whether their colleague was responding honestly to them or lying to them. Experiment 2 compared untrained officers to officers trained in Assessment Criteria Indicative of Deception (ACID) in their ability to assess the credibility of statements regarding real and mock crimes by analyzing either verbatim transcripts or audio recordings. Officers who were trained in ACID performed significantly better after training than before, and significantly better than a group of officers who were never trained in ACID (89% correct versus 53% correct). No differences emerged due to analyzing transcripts versus recordings. The practical aspects of these results are discussed, including success rate, ease of application, and ease of training. The theoretical discussion includes differential recall enhancement and impression management. Finally, limitations and suggestions for future research are presented.
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/172-830-993-603-666 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Article; Assessment Criteria Indicative of Deception (ACID); adult; assessment criteria indicative of deception; audio recording; clinical assessment tool; controlled study; credibility assessment; criminal justice; deception; decision making; dept.psy; diagnostic accuracy; differential recall enhancement; human; human experiment; investigative interviewing; police; recall; scoring system; task performance; training; verbal behavior; videorecording; visual stimulation; word recognition; written language

Prenatal ethanol increases ethanol intake throughout adolescence, alters ethanol-mediated aversive learning, and affects μ but not δ or κ opioid receptor mRNA expression - Fabio, María Carolina; Macchione, Ana Fabiola; Nizhnikov, Michael E.; Pautassi, Ricardo Marcos (European Journal of Neuroscience, 2015)
Animal models of prenatal ethanol exposure (PEE) have indicated a facilitatory effect of PEE on adolescent ethanol intake, but few studies have assessed the effects of moderate PEE throughout adolescence. The mechanisms underlying this facilitatory effect remain largely unknown. In the present study, we analysed ethanol intake in male and female Wistar rats with or without PEE (2.0 g/kg, gestational days 17-20) from postnatal days 37 to 62. The results revealed greater ethanol consumption in PEE rats than in controls, which persisted throughout adolescence. By the end of testing, ethanol ingestion in PEE rats was nearly 6.0 g/kg. PEE was associated with insensitivity to ethanol-induced aversion. PEE and control rats were further analysed for levels of μ, δ and κ opioid receptor mRNA in the infralimbic cortex, nucleus accumbens shell, and ventral tegmental area. Similar levels of mRNA were observed across most areas and opioid receptors, but μ receptor mRNA in the ventral tegmental area was significantly increased by PEE. Unlike previous studies that assessed the effects of PEE on ethanol intake close to birth, or in only a few sessions during adolescence, the present study observed a facilitatory effect of PEE that lasted throughout adolescence. PEE was associated with insensitivity to the aversive effect of ethanol, and increased levels of μ opioid receptor transcripts. PEE is a prominent vulnerability factor that probably favors the engagement of adolescents in risky trajectories of ethanol use. © 2015 Federation of European Neuroscience Societies and John Wiley & Sons Ltd.
45 citations (Crossref) [2023-10-31] Citation Key Alias: pop00123 tex.type: [object Object]
Keywords: *Alcohol Drinking/pp [Physiopathology]; *Avoidance Learning/de [Drug Effects]; *Central Nervous System Depressants/to [Toxicity]; *Ethanol/to [Toxicity]; *Prenatal Exposure Delayed Effects/ci [Chemically Induced]; *Receptors; Opioid; delta/me [Metabolism]; *Receptors; Opioid; kappa/me [Metabolism]; Adolescent; Age Factors; Alcohol Drinking; Animals; Article; Aversive conditioning; Avoidance Learning; Central Nervous System Depressants; Ethanol; Ethanol intake; Female; Male; Opioid receptors; Pregnancy; Prenatal Exposure Delayed Effects; Prenatal Exposure Delayed Effects/pp [Physiopathology]; Prenatal ethanol; RNA isolation; RNA; Messenger; RNA; Messenger/me [Metabolism]; Rats; Rats; Wistar; Receptors; Opioid; delta; Receptors; Opioid; delta/ge [Genetics]; Receptors; Opioid; kappa; Receptors; Opioid; kappa/ge [Genetics]; Wistar rat; adolescence; adolescent; age; alcohol; alcohol consumption; alcohol intoxication; animal; animal experiment; animal model; aversion; aversive behavior; aversive conditioning; avoidance behavior; body weight; central depressant agent; chemically induced; controlled study; delta opiate receptor; dept.psy; drinking behavior; drug effects; ethanol intake; facilitation; female; fluid intake; genetics; glyceraldehyde 3 phosphate dehydrogenase; kappa opiate receptor; male; messenger RNA; metabolism; microdissection; motivation; mu opiate receptor; nonhuman; opioid receptors; pathophysiology; place preference; polymerase chain reaction; pregnancy; prenatal ethanol; prenatal ethanol exposure; prenatal exposure; priority journal; protein expression; quantitative analysis; rat; reinforcement; reverse transcription; sigma opiate receptor; sugar intake

Differential emotions theory as a theory of personality development - Abe, Jo Ann A. (Emotion Review, 2015)
In The Face of Emotions, which was Carroll Izard's first major attempt at elaborating his differential emotions theory (DET), he stated that the book presents a theoretical framework for the study of emotions and their role in personality and interpersonal processes. Yet, over the years, his contribution to personality theory has generally been overshadowed by the attention focused on his views on facial expressions and the structure of emotions. This article will begin with a brief overview of the DET perspective on personality development. Then, it will examine how the DET framework can be used to organize recent findings from three lines of research on adult personality. It will conclude with suggestions for future research as well as some personal recollections.
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/140-465-546-229-306 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.psy; differential emotions theory; emotions; personality development

Introduction: special section to honor carroll izard - Abe, Jo Ann A.; Schultz, David (Emotion Review, 2015)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/152-927-568-508-807 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.psy

Endogenous opioids as substrates for ethanol intake in the neonatal rat: The impact of prenatal ethanol exposure on the opioid family in the early postnatal period. - Bordner, Kelly; Deak, Terrence (Physiology & Behavior, 2015)
BACKGROUND: Despite considerable knowledge that prenatal ethanol exposure can lead to devastating effects on the developing fetus, alcohol consumption by pregnant women remains strikingly prevalent. Both clinical and basic research has suggested that, in addition to possible physical, behavioral, and cognitive deficits, gestational exposure to alcohol may lead to an increased risk for the development of later alcohol-related use and abuse disorders. The current work sought to characterize alterations in endogenous opioid signaling peptides and gene expression produced by ethanol exposure during the last days of gestation., METHODS: Experimental subjects were 4-, 8-, and 12-day old infant rats obtained from pregnant females that were given daily intubations of 0, 1, or 2g/kg ethanol during the last few days of gestation (GDs 17-20). Using real-time RT-PCR, western blotting analysis, and enzyme immunoassays, we examined mRNA and protein for three opioid receptors and ligands in the nucleus accumbens, ventral tegmental area, and hypothalamus., RESULTS: Three main trends emerged - (1) mRNA for the majority of factors was found to upregulate across each of the three postnatal ages assessed, indicative of escalating ontogenetic expression of opioid-related genes; (2) prenatal ethanol significantly reduced many opioid peptides, suggesting a possible mechanism by which prenatal exposure can affect future responsiveness towards ethanol; and (3) the nucleus accumbens emerged as a key site for ethanol-dependent effects, suggesting a potential target for additional assessment and intervention towards understanding the ethanol's ability to program the developing brain., CONCLUSION: We provide a global assessment of relatively long-term changes in both opioid gene expression and protein following exposure to only moderate amounts of ethanol during a relatively short window in the prenatal period. These results suggest that, while continuing to undergo ontogenetic changes, the infant brain is sensitive to prenatal ethanol exposure and that such exposure may lead to relatively long-lasting changes in the endogenous opioid system within the reward circuitry. These data indicate a potential mechanism and target for additional assessments of ethanol's ability to program the brain, affecting later responsiveness towards the drug. Copyright © 2015 Elsevier Inc. All rights reserved.
23 citations (Crossref) [2023-10-31] Place: United States Bordner, Kelly. Department of Psychology, Southern Connecticut State University, New Haven, CT 06515, United States; Behavioral Neuroscience Program, Department of Psychology, Binghamton University-SUNY, Binghamton, NY 13902, United States. Electronic address: bordnerk2@southernct.edu. Deak, Terrence. Behavioral Neuroscience Program, Department of Psychology, Binghamton University-SUNY, Binghamton, NY 13902, United States; Developmental Exposure Alcohol Research Center (DEARC), Center for Development and Behavioral Neuroscience, Binghamton University-SUNY, Binghamton, NY 13902, United States.
Keywords: *Alcohol Drinking/pp [Physiopathology]; *Central Nervous System Depressants/pd [Pharmacology]; *Ethanol/pd [Pharmacology]; *Gene Expression Regulation; Developmental/de [Drug Effects]; *Prenatal Exposure Delayed Effects/pp [Physiopathology]; *Receptors; Opioid/me [Metabolism]; Age Factors; Alcohol Drinking; Analysis of Variance; Animals; Animals; Newborn; Article; Brain; Brain/gd [Growth & Development]; Brain/me [Metabolism]; Central Nervous System Depressants; Dynorphins; Dynorphins/ge [Genetics]; Dynorphins/me [Metabolism]; Enkephalins; Enkephalins/ge [Genetics]; Enkephalins/me [Metabolism]; Ethanol; Female; Gene Expression Regulation; Developmental; Gestational Age; MRNA; Male; Ontogeny; Opioids; Pregnancy; Prenatal Exposure Delayed Effects; Pro-Opiomelanocortin; Pro-Opiomelanocortin/ge [Genetics]; Pro-Opiomelanocortin/me [Metabolism]; Protein; Protein Precursors; Protein Precursors/ge [Genetics]; Protein Precursors/me [Metabolism]; RNA; Messenger; RNA; Messenger/me [Metabolism]; Rat; Rats; Rats; Sprague-Dawley; Receptors; Opioid; Receptors; Opioid/ge [Genetics]; Sprague Dawley rat; Western blotting; age; alcohol; alcohol consumption; analysis of variance; animal; animal experiment; animal tissue; beta endorphin; brain; brain development; central depressant agent; controlled study; delta opiate receptor; dept.psy; drinking behavior; drug effects; dynorphin; endorphin; enkephalin; enzyme immunoassay; female; gene expression; gene expression regulation; genetics; gestation period; gestational age; growth; development and aging; hypothalamus; infant; kappa opiate receptor; male; messenger RNA; metabolism; mu opiate receptor; newborn; nonhuman; nucleus accumbens; ontogeny; opiate receptor; pathophysiology; peer-reviewed; perinatal period

Change in the hedonic value of an aversive stimulus in the presence of a pre-exposed odor. - Kamenetzky, Giselle V; Suarez, Andrea B; Pautassi, Ricardo M; Mustaca, Alba E; Nizhnikov, Michael E (Physiology & behavior, 2015)
Rats exhibit a sensitive period from the time of birth until postnatal day 10 during which they develop preferences for odors even if those odors are paired with a moderately aversive stimulus. It is still unknown whether pre-exposure to an odor produces alterations on intake responses of basic tastants, and on other patterns that indicate a change in the hedonic value of reward, such as nipple grasping behavior. The current study assessed the effect of pre-exposure to an odor immediately after birth on intake responses of appetitive and aversive tastants. The objectives were to assess if 3-hour-old rats adjust their behaviors to obtain different values of appetitive and aversive rewards in the presence of a familiar odor. Specifically we wanted to determine whether the intake of saccharin or quinine, administered through the artificial nipple, increases in the presence of the familiar odor. Results showed that 3-hour-old rats differentially respond to two different concentrations of saccharin and two concentrations of quinine. In the presence of the pre-exposed odor newborn rats increased intake and grasp responses to the artificial nipple containing quinine. This effect disappeared with a higher concentration of quinine. These results suggest that the pre-exposed odor generated a change in the hedonic value of the aversive reward. Copyright © 2014 Elsevier Inc. All rights reserved.
12 citations (Crossref) [2023-10-31] Place: United States Kamenetzky, Giselle V. Laboratorio de Psicologia Experimental y Aplicada, IDIM, CONICET, UBA, Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Electronic address: yoselevich@hotmail.com. Suarez, Andrea B. Laboratorio de Psicologia Experimental y Aplicada, IDIM, CONICET, UBA, Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Pautassi, Ricardo M. Instituto de Investigacion Medica Mercedes y Martin Ferreyra, CONICET, Universidad Nacional de Cordoba, Cordoba, Argentina. Mustaca, Alba E. Laboratorio de Psicologia Experimental y Aplicada, IDIM, CONICET, UBA, Centro de Altos Estudios en Ciencias Humanas y de la Salud (CAECIHS-UAI), Universidad Abierta Interamericana, Buenos Aires, Argentina. Nizhnikov, Michael E. Southern Connecticut State University, United States.
Keywords: *Avoidance Learning/ph [Physiology]; *Conditioning; Psychological/ph [Physiology]; *Discrimination; Psychological/ph [Physiology]; *Emotions/ph [Physiology]; *Odorants; *Smell/ph [Physiology]; Age Factors; Analgesics; Non-Narcotic; Animals; Animals; Newborn; Appetitive Behavior; Appetitive Behavior/ph [Physiology]; Article; Aversive solutions; Avoidance Learning; Conditioning (Psychology); Discrimination (Psychology); Dose-Response Relationship; Drug; Emotions; Female; Male; Newborn rats; Odors; Olfactory learning; Ontogeny; Quinine; Quinine/ad [Administration & Dosage]; Rats; Rats; Sprague-Dawley; Reaction Time; Reaction Time/de [Drug Effects]; Reaction Time/ph [Physiology]; Saccharin; Saccharin/ad [Administration & Dosage]; Smell; Sprague Dawley rat; Sweetening Agents; age; analgesic agent; animal; animal behavior; animal experiment; appetite; aversion; avoidance behavior; birth; bitter taste; conditioning; controlled study; dept.psy; dose response; drug effects; emotion; exposure; female; food intake; grip strength; gustatory system; male; newborn; nipple; nonhuman; odor; peer-reviewed; perceptive discrimination; physiology; priority journal; quinine; rat; reaction time; reward; saccharin; stimulus; sweetening agent; taste

Can low-level ethanol exposure during pregnancy influence maternal care? An investigation using two strains of rat across two generations. - Popoola, Daniel O; Borrow, Amanda P; Sanders, Julia E; Nizhnikov, Michael E; Cameron, Nicole M (Physiology & behavior, 2015)
Gestational alcohol use is well documented as detrimental to both maternal and fetal health, producing an increase in offspring's tendency for alcoholism, as well as in behavioral and neuropsychological disorders. In both rodents and in humans, parental care can influence the development of offspring physiology and behavior. Animal studies that have investigated gestational alcohol use on parental care and/or their interaction mostly employ heavy alcohol use and single strains. This study aimed at investigating the effects of low gestational ethanol dose on parental behavior and its transgenerational transmission, with comparison between two rat strains. Pregnant Sprague Dawley (SD) and Long Evans (LE) progenitor dams (F0) received 1g/kg ethanol or water through gestational days 17-20 via gavage, or remained untreated in their home cages. At maturity, F1 female offspring were mated with males of the same strain and treatment and were left undisturbed through gestation. Maternal behavior was scored in both generations during the first six postnatal days. Arch-back nursing (ABN) was categorized as: 1, when the dam demonstrated minimal kyphosis; 2, when the dam demonstrated moderate kyphosis; and 3, when the dam displayed maximal kyphosis. Overall, SD showed greater amounts of ABN than LE dams and spent more time in contact with their pups. In the F0 generation, water and ethanol gavage increased ABN1 and contact with pups in SD, behaviors which decreased in treated LE. For ABN2, ethanol-treated SD dams showed more ABN2 than water-treated dams, with no effect of treatment on LE animals. In the F1 generation, prenatal exposure affected retrieval. Transgenerational transmission of LG was observed only in the untreated LE group. Strain-specific differences in maternal behavior were also observed. This study provides evidence that gestational gavage can influence maternal behavior in a strain-specific manner. Our results also suggest that the experimental procedure during gestation and genetic variations between strains may play an important role in the behavioral effects of prenatal manipulations. Copyright © 2015 Elsevier Inc. All rights reserved.
16 citations (Crossref) [2023-10-31] Place: United States Popoola, Daniel O. Psychology Department, Center for Development and Behavioral Neuroscience, Binghamton University - SUNY, NY, USA. Borrow, Amanda P. Psychology Department, Center for Development and Behavioral Neuroscience, Binghamton University - SUNY, NY, USA. Sanders, Julia E. Psychology Department, Center for Development and Behavioral Neuroscience, Binghamton University - SUNY, NY, USA. Nizhnikov, Michael E. Psychology Department, Southern Connecticut State University, CT, USA. Cameron, Nicole M. Psychology Department, Center for Development and Behavioral Neuroscience, Binghamton University - SUNY, NY, USA. Electronic address: ncameron@binghamton.edu.
Keywords: *Central Nervous System Depressants/to [Toxicity]; *Ethanol/to [Toxicity]; *Maternal Behavior; *Prenatal Exposure Delayed Effects/ci [Chemically Induced]; Alcohol Drinking; Alcohol Drinking/pp [Physiopathology]; Analysis of Variance; Animals; Animals; Newborn; Article; Central Nervous System Depressants; Ethanol; Female; Grooming; Intragastric gavage; Long Evans rat; Male; Maternal Behavior; Maternal care; Posture; Pregnancy; Prenatal Exposure Delayed Effects; Prenatal Exposure Delayed Effects/nu [Nursing]; Prenatal Exposure Delayed Effects/pp [Physiopathology]; Rat; Rats; Rats; Long-Evans; Rats; Sprague-Dawley; Species Specificity; Sprague Dawley rat; Time Factors; Transgenerational; alcohol; alcohol consumption; analysis of variance; animal; animal experiment; animal model; body posture; central depressant agent; chemically induced; controlled study; dept.psy; drinking behavior; female; genetic variability; grooming; kyphosis; licking; male; maternal behavior; maternal care; mating; newborn; nonhuman; nursing; parental behavior; pathophysiology; peer-reviewed; pregnancy; prenatal exposure; priority journal; progeny; rat; species difference; time

Development of an audiovisual speech perception app for children with autism spectrum disorders - Irwin, Julia; Preston, Jonathan; Brancazio, Lawrence; D'Angelo, Michael; Turcios, Jacqueline (Clinical Linguistics & Phonetics, 2015)
Perception of spoken language requires attention to acoustic as well as visible phonetic information. This article reviews the known differences in audiovisual speech perception in children with autism spectrum disorders (ASD) and specifies the need for interventions that address this construct. Elements of an audiovisual training program are described. This researcher-developed program delivered via an iPad app presents natural speech in the context of increasing noise, but supported with a speaking face. Children are cued to attend to visible articulatory information to assist in perception of the spoken words. Data from four children with ASD ages 8-10 are presented showing that the children improved their performance on an untrained auditory speech-in-noise task.
16 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/022-073-168-350-692 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Attention; Audiovisual Aids; Audiovisual app; Autism spectrum disorder; Child; Child Development Disorders; Pervasive; Comprehension; Humans; Lipreading; Male; Mobile Applications; Pattern Recognition; Visual; Phonetics; Semantics; Speech Perception; Speech perception; attention; audiovisual aid; child; comprehension; dept.cmd; dept.hls; dept.psy; human; lip reading; male; mobile application; pattern recognition; phonetics; psychology; semantics; speech perception